Effects of small scale irrigation on women farmers’ well-being status in Sikasso region of Mali (2020)
This study examined effects of small scale irrigation on women farmers’ well-being status in Sikasso Region of Mali. A multi-stage sampling procedure was used to select 160 respondents (user and non-users) while data were collected using interview schedules and analysed using percentages, mean, standard deviation and t-test. Major constraints facing users are crop damage (x̅ =2.68), unavailability of input (x̅ =2.41) and inadequate credit facility (x̅ =2.15). Sixty percent, 98.8%, 85.0%, 85.0% of users have higher level of material, economic, mental and social well-being, respectively compared to 25%, 0.0%, 68.8% and 35.0% of non-users with similar status. The overall wellbeing of 73.8% of users were better-off compared to 11.3% of non-users. A significant difference (t= 11.110) existed in the wellbeing status of users and non-users. Utilisation of small-scale irrigation systems had positive effects on the mental, social, economic and material wellbeing of the users. There is need to extend small scale irrigation to non-users.